Towards a better understanding of parallel visual processing in human vision: Evidence for exhaustive analysis of visual information. - Buetti, Simona; Cronin, Deborah A.; Madison, Anna M.; Zhiyuan Wang; Lleras, Alejandro (Journal of Experimental Psychology. General, 2016)
Most current models of visual processing propose that there are 2 main stages of visual processing, the first consisting of a parallel visual analysis of the scene and the second being a precise scrutiny of a few elements in the scene. Here, we present novel evidence that the first stage of processing adds systematic variance to visual processing times. When searching for a specific target, it has a behaviorally unique signature: RTs increase logarithmically with the number of items in the display and this increase is modulated by target-distractor similarity. This signature is characteristic of unlimited capacity parallel and exhaustive processing of all the elements in the scene. The function of this processing is to identify the locations in the scene containing items that are sufficiently similar to the target as to merit focused scrutiny, while discarding those that do not. We also demonstrate that stage-1 variability is sensitive to the observers' top-down goals: with identical displays, whereas RTs increase logarithmically with set size when observers are asked to find a specific target, they decrease exponentially when asked to find a unique item in the scene.